iSnap assist 1.0 (Raspberry ZeroW) - Tan, Theodore Wan Li (Nanyang Technological University, 2024)
High-speed photography is a method of capturing photographs, such as water splashes or the bursting of a water-filled balloon. All these pictures had a brief duration before disappearing, lasting less than a split second. In other words, individuals may be unable to see that sight if they do not direct their attention towards it at the moment when it takes place. To get these images, the photographer must exercise patience and swiftly push the shutter to catch the scene in real-time. This task often requires a significant amount of effort and time.